(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
One of the advanced technologies used in the communicating systems of the intelligent grid is Wireless Sensor Network (WSN). WSN has a wide range of applications covers many fields like catastrophe management, hostilities field recognition, border insurance, patient health monitoring, and others. The sensor connectivity and coverage problems recently have a great attention. In this paper, we presented the connectivity and coverage of nodes in WSN, a new algorithm is prepared to extract exact coverage area of plain uniform depletion of node samples according to simple disk model. This algorithm considers the connection of nodes within maximum range of transmission communications, therefore no disconnected graph occurs. While uncovered area within region of interest (RoI) inside coverage area is calculated, although many uncovered regions occurred. So the coverage percentage area is calculated in an exact solution. This algorithm will be one of keystone study to better control of sensor depletion.